Pt-Containing Ag2S-Noble Metal Nanocomposites as Highly Active Electrocatalysts for the Oxidation of Formic Acid - Liu, Hui; Feng, Yan; Cao, Hongbin; Yang, Jun (Nano-Micro Letters, 2014)
Nanocomposites with synergistic effect are of great interest for their enhanced properties in a given application. Herein, we reported the high catalytic activity of Pt-containing Ag2S-noble metal nanocomposites in formic acid oxidation, which is a key reaction in direct formic acid fuel cell. The electrochemical measurements including voltammograms and chronoamperograms are used to characterize the catalytic property of Pt-containing nanocomposites for the oxidation of formic acid. In view of the limited literatures on using nanocomposites consisting of semiconductor and noble metals for catalyzing the reactions of polymer electrolyte membrane-based fuel cells, this study provides a helpful exploration for expanding the application of semiconductor-noble metal nanocomposites.